Strategi Komunikasi Guru terhadap Siswa Berkebutuhan Khusus Kelas III dalam Proses Belajar Mengajar di SLB YPAC Medan - Norma Amaliah; Zuhriah Zuhriah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Communication is a crucial element in the learning process, particularly in the education of students with special needs who possess diverse characteristics, abilities, and communication requirements. These differences require teachers to implement adaptive communication strategies to ensure that learning messages are effectively conveyed and understood by students. This study aims to analyze the communication at SLB YPAC Medan. The subjects of this study specifically focused on third-grade students with intellectual disabilities (tunagrahita) and slow learners. The. The study adopted a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that teachers apply communication strategies through a combination of verbal and nonverbal communication. Verbal communication involves the use of simple language, repetition of learning materials, and step-by-step instructions tailored to students’ abilities. Meanwhile, nonverbal communication is expressed through facial expressions, body movements, eye contact, and the use of visual learning media to clarify instructional messages. In addition, interpersonal approaches emphasizing patience, attention, empathy, and emotional closeness were found to enhance the effectiveness of teacher–student interactions. Supporting factors include adequate school facilities, psychological services, and therapy programs, while inhibiting factors involve differences in students’ characteristics and limitations in their communication abilities. This study concludes that adaptive communication strategies that accommodate individual student needs play a significant role in creating an effective, comfortable, and supportive learning environment for students with special needs.